1992
DOI: 10.3928/0147-7447-19920301-15
|View full text |Cite
|
Sign up to set email alerts
|

Low Lumbar Burst Fractures: Comparison Between Conservative and Surgical Treatments

Abstract: Twenty-two low lumbar burst fractures (L3-L5) were treated, with an average follow up of 56.2 and 39.0 months in the conservative and surgically treated groups, respectively. Twenty patients were available for review; seven were treated conservatively and 13 were stabilized surgically. All patients were evaluated clinically for work status, activity level, residual pain, and subsequent development of neurologic symptoms. Roentgenograms were reviewed for severity of initial fracture, canal compromise, and maint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(5 citation statements)
references
References 25 publications
0
4
0
1
Order By: Relevance
“…SSPF has recently gained popularity due to a theoretical reduction in surgery time and implant expenses and the potential to save more motion segments [ 23 , 30 , 31 ]. According to some studies, SSPF is the best option for flatback disorder and loss of lumbar lordosis [ 32 ]. In addition, the main drawbacks of the procedure were insufficient lengthy reduction and instrumentation failure with postoperative kyphosis [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…SSPF has recently gained popularity due to a theoretical reduction in surgery time and implant expenses and the potential to save more motion segments [ 23 , 30 , 31 ]. According to some studies, SSPF is the best option for flatback disorder and loss of lumbar lordosis [ 32 ]. In addition, the main drawbacks of the procedure were insufficient lengthy reduction and instrumentation failure with postoperative kyphosis [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Verlaan et al (29) has reported that surgical treatment of traumatic spine fractures is safe and effective. In their studies An et al (30) and Smith et al (31) has stated that short rigid fixation with pedicular instrumentation is more beneficial in surgical treatment of spine fractures. There are also different studies (32)(33)(34)(35) in the literature that support the research results and draw attention to the safety of the use of short-segment pedicle instrumentation.…”
Section: Discussionmentioning
confidence: 99%
“…In 1992, An et al 6 compared conservative and surgical treatment of low lumbar burst fractures. This study concluded that the use of long segment instrumentation and fusion in treating these injuries should be avoided and that many of these fractures are amenable to conservative therapy, especially if the patient is neurologically intact.…”
Section: Discussionmentioning
confidence: 99%
“…3). Pain levels were classified as either none, mild, moderate, or severe, a scale previously used in examining low lumbar fractures, 6 and determined by the patients' reports in clinic at final follow-up.…”
Section: Postoperative Managementmentioning
confidence: 99%